Differences in the perceived role of the healthcare provider in delivering vascular health checks: a Q methodology study - Honey, Stephanie (BioMed Central, 2013)
BACKGROUND: The UK Department of Health introduced the National Health Service (NHS) Health Check Programme in April 2009 in an attempt to improve primary and secondary prevention of cardiovascular disease in the UK population and to reduce health inequalities. Healthcare professionals' attitudes towards giving lifestyle advice will influence how they interact with patients during consultations. We therefore sought to identify the attitudes of primary care healthcare professionals towards the delivery of lifestyle advice in the context of the NHS Health Check Programme. METHODS: Fifty-two primary care healthcare professionals undertook a Q sort with 36 statements that represented a range of viewpoints about the importance of lifestyle change, medication, giving lifestyle advice in the primary care setting, and the individual, social and material factors that might impact on lifestyle related behaviour change. Sorts were analysed by-person using principal components analysis and varimax rotation. RESULTS: Five statistically independent factors (accounts) reflected distinct views on the topic. Account 1 was supportive of initiatives like the NHS Health Check, and emphasised the importance of professionals working collaboratively with patients to facilitate lifestyle change. Account 2 expressed views on the potential overuse of statin medication and placed responsibility for lifestyle change with the patient. Account 3 viewed the healthcare professional role to be one of educator, emphasising the provision of information. Account 4 perceived lifestyle change to be difficult for patients and emphasised the need for healthcare professionals to be role models. Account 5 was inconsistent about the value of lifestyle change, or the role of healthcare professionals in promoting it, a finding that may be due to ambivalence about the health check or to lack of engagement with the Q sort task. We found no strong associations between any of the factors and, gender, role, age or ethnicity. CONCLUSIONS: Our findings suggest that healthcare professionals hold viewpoints that may influence how they interact with patients during health checks. When implementing programmes like the NHS Health Check, it would be useful to take healthcare professionals’ views into account. Attitudes and beliefs could be explored during training sessions, for example.